2011
DOI: 10.3171/2011.5.spine10748
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of ossification of the ligamentum flavum associated with dural ossification

Abstract: Object In this paper, the authors aimed to summarize the clinical characteristics of ossification of the ligamentum flavum (OLF) associated with dural ossification (DO) and to identify improved methods for preoperative diagnosis. Methods Thirty-six patients who had undergone OLF surgery between February 2005 and September 2009 were included in this retrospective study. The patients were divided into 2 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 20 publications
1
49
0
1
Order By: Relevance
“…The intraoperative manipulation should be gentle to avoid dural tears as much as possible, and once a dura mater tear is noticed, immediate repair should be carried out. 56,68,70 Eight cases underwent dura mater repair and no CSF leakage happened after the operation, and the surgical effect was satisfactory. Although the procedure and success of intraoperative repair is important, comprehensive treatments after operation should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intraoperative manipulation should be gentle to avoid dural tears as much as possible, and once a dura mater tear is noticed, immediate repair should be carried out. 56,68,70 Eight cases underwent dura mater repair and no CSF leakage happened after the operation, and the surgical effect was satisfactory. Although the procedure and success of intraoperative repair is important, comprehensive treatments after operation should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68] Because dural adhesion and DO are more common in thoracic OLF than in cervical or lumbar spine, the incidence of CSF leakage in OLF patients may be higher. 56,[68][69][70] Miyakoshi et al 56 reported that dural adhesion was observed in 62% of the 34 patients with OLF, and found that dural adhesion was frequently observed in larger types of OLF. Aizawa et al 11 reported that 9 of 72 patients with OLF had dual tears during surgery and 8 of them had DO.…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the relatively small study population and lack of awareness of these specific image signs accurate diagnosis of DO could not be obtained in previous studies 210 Since the incidence of OLF and DO is relatively low, few studies have focused on this issue 29 10 The incidence and distribution of DO were also unclear.…”
Section: Introductionmentioning
confidence: 99%
“…10 Since the incidence of OLF and DO is relatively low, few studies have focused on this issue 29 10 The incidence and distribution of DO were also unclear. The present study aimed to investigate the incidence, distribution and radiological characteristics of DO in thoracic OLF.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure of the epidural venous plexus and dural pulsation are considered to contribute to this phenomenon [30]. Dural ossification develops in 11% to 40% [15,[31][32][33][34][35]. There are two CT findings which predict dural ossification.…”
Section: Treatment and Prognosismentioning
confidence: 99%